Abdominal Leiomyoma in an Adult Transgender with Adrenogenital Syndrome: A Rare Case Report - AlAni, Ahmed Mansour M.; Al Mukdad, Omar; Hassan, Yosra M. El khatem Ahmed; Al-bozom, Issam; Zabara, Abdulwahab; Alfared, Mohamed H.; Kolleri, Jouhar J.; Darweesh, Adham (AL-Kindy College Medical Journal, 2025)
Leiomyomas of the abdomen are rare intra-abdominal tumors, particularly in male patients with adrenal hyperplasia. We report the case of a 50-year-old considers himself a with a man, who was born as a female, and has several surgeries related to transitioning from intersex to male gender. These procedures include bilateral oophorectomy with silicone testicular implantation, bilateral mastectomy with closure of the labial cleft, reconstruction of the urethral canal, and placement of testicular implants. He has a wife and two adopted children. The patient presented to the emergency department suffering from lower abdominal pain and vomiting. On examination, the abdomen appeared distended and soft. In addition to positive bowel sounds, there is a palpable large, firm, slightly tender mass occupying the lower abdomen and extending above the umbilicus, a small penis, and bilateral suspected testes in the proximal inguinal region. Abdominal radiographs, abdominal ultrasounds, and computer tomography (CT) of the abdomen and pelvis with intravenous contrast revealed a large pelvic-abdominal mass, bilaterally enlarged adrenal glands, and bilaterally implanted tests seen in the inguinal region. An ultrasound-guided tissue biopsy and an exploratory laparotomy were performed, and the tumor was completely resected. A rounded, firm mass arises from the pelvis, with histopathology revealing its origin from the remnants of the uterus and vaginal adhesions adherent to the mesentery. A tissue biopsy confirmed the leiomyoma